Labor Productivity of Independent Palm Oil Farming in Central Lampung - Lestari, Dyah Aring Hepiana; Arifin, Bustanul; Aristiyani, Ririn (Jurnal AGRISEP, 2025)
This study aims to analyze the level of labour productivity and the factors influencing labour productivity in independent oil palm plantations. The research has taken place in Bangunrejo Sub-district, Central Lampung Regency. Data collection used the survey method. The sample size was 70 independent oil palm farmers. Sampling of oil palm farmers using a stratified random sampling method according to the age of the oil palm plants. Based on the conditions at the research location, the age of the plants is categorized into 19-12 years, 13-16 years, 17-21 years, 22-25 years. The sample size of each age category is 8, 14, 24 and 24 farmers. Data analysis employed descriptive quantitative methods and multiple linear regression. The results revealed that there is a tendency that the older the plant, the higher the labour productivity. The level of labour productivity in independent oil palm farms in the 9–12 year plant age group was  247.40 kg TBS/HOK, 13–16 year plant age was  250.81 kg TBS/HOK, 17–21 year plant age was 230.70 kg TBS/HOK, and 22–25 year plant age was  253.95 kg TBS/HOK. This is reinforced by the results of the regression analysis, which shows that when the land size, farming experience, and age of oil palm plants increase, the labour productivity of independent oil palm farms also increases.